2017
DOI: 10.1177/1591019917694839
|View full text |Cite
|
Sign up to set email alerts
|

A hemorrhagic complication after Onyx embolization of a tentorial dural arteriovenous fistula: A caution about subdural extension with pial arterial supply

Abstract: We report a case of tentorial dural arteriovenous fistula (DAVF) with a severe intracranial hemorrhage occurring after Onyx embolization. A 40-year-old man presented with an asymptomatic tentorial DAVF on angiography. Transarterial embolization with Onyx was performed via the middle meningeal artery, and the cast filled the fistula itself and its proximal draining vein. Postoperative angiography confirmed complete occlusion of the DAVF. A computed tomography scan performed immediately after the proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…Hemorrhagic complication after the endovascular treatment of the DAVFs has been reported in recent literatures with an incidence rate of 0-3.8%. 2,3 In this study, the hemorrhagic complication rate after the endovascular embolization was 4.5% (12/267), which was not eligible in DAVF treatment. In 2017, Sadeh-Gonike U et al 5 of all previous transarterial embolization studies using Onyx published between January 2005 and December 2015 and found the rate of hemorrhagic complications rate was 0%.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Hemorrhagic complication after the endovascular treatment of the DAVFs has been reported in recent literatures with an incidence rate of 0-3.8%. 2,3 In this study, the hemorrhagic complication rate after the endovascular embolization was 4.5% (12/267), which was not eligible in DAVF treatment. In 2017, Sadeh-Gonike U et al 5 of all previous transarterial embolization studies using Onyx published between January 2005 and December 2015 and found the rate of hemorrhagic complications rate was 0%.…”
Section: Discussionmentioning
confidence: 73%
“…DAVFs with pial venous drainage or venous aneurysm are risk factors for hemorrhagic presentation in patients with DAVF. [2][3][4] Management of DAVFs includes open surgery, radiosurgery, endovascular embolization, or a combination of these modalities. Endovascular Onyx embolization has now been accepted as the primary treatment strategy to manage DAVFs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports of hemorrhagic complications with transarterial Onyx embolization of intracranial dural AVFs with pial feeder. 12,13 However, all of the reported three cases were located in the tentorium and associated with special angioarchitecture, which may not apply to CCJ AVFs; one had drainage into the vein of Galen and the basal vein of Rosenthal with venous varix, another had pathologically demonstrated vascular malformation and the other had subdural extension of glomus-like vasculature. In fact, the previous case report successfully treated CCJ epidural AVF with a pial feeder aneurysm by clipping venous outlet without hemorrhage.…”
Section: Discussionmentioning
confidence: 98%
“…The target of this treatment regimen is complete occlusion of the fistula with cortical venous reflux ( 24 ). During endovascular embolization, if the embolic agent completely occludes the fistula by crossing into the immediate receptive venous structure, an adequate outcome can be achieved ( 56 ). Endovascular embolization may be performed using different types of embolic agents and a variety of routes.…”
Section: Treatmentmentioning
confidence: 99%